Real-world study of adebrelimab as first-line therapy for extensive-stage small cell lung cancer: a retrospective study - Xu, Kaili; Wang, Jian; Weng, Zhenhe; Wang, Junhui; Chen, Jianxin (Frontiers in Immunology, 2025)
BackgroundExtensive-stage small cell lung cancer (ES-SCLC) has a poor prognosis, with historical median overall survival (OS) of 8–13 months under platinum-etoposide chemotherapy. While phase III trials established adebrelimab (anti-PD-L1) plus chemotherapy as a new standard, real-world evidence remains scarce. This study evaluated real-world efficacy, safety, and prognostic factors of first-line adebrelimab-based therapy.MethodsIn this retrospective study, thirty-five patients with ES-SCLC receiving adebrelimab as first-line treatment were analyzed. Endpoints included objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), OS, and adverse events (AEs). Prognostic factors were assessed via Cox regression.ResultsMedian age was 72 years; 88.6% were male, 85.7% had Eastern Cooperative Oncology Group Performance Status (ECOG PS) 0–1, and 51.4% had ≥2 metastatic sites. ORR was 62.8%, DCR 77.1%. Median PFS was 7.1 months (95% CI: 5.47–8.53), and median OS was 15.0 months (95% CI: 10.47–19.53). Multivariate analysis identified ECOG PS ≥2 as an independent predictor of inferior PFS (HR = 9.446, p=0.013), while ≥2 metastatic organs (HR = 3.594, p=0.046) and C-reactive Protein (CRP) ≥5 mg/L (HR = 3.337, p=0.044) predicted worse OS. Grade 3–4 AEs occurred in 74.3% of patients, primarily hematologic toxicities (neutropenia: 51.4%); two cases (5.7%) of myocarditis were observed.ConclusionsAdebrelimab suggests potentially promising efficacy in ES-SCLC, aligning with pivotal trial data despite an older cohort. ECOG PS ≥2, high metastatic burden, and elevated CRP independently predict poorer outcomes. Vigilant monitoring for hematologic toxicity and rare cardiotoxicity is warranted.